Ending party cleavage for a better polity: is Kwasi Wiredu’s non-party polity a viable alternative to a party polity? (Acta Academica, 2016)
Africa’s current democratic outlook is a relic of the crowning vestige bequeathed by the colonial metropolis as a sign of the African’s attainment of political freedom. As if to suggest that at the occasion of the attainment of that freedom, the African had become human, the metropolis demanded that formerly colonised territories had to democratise. This democratisation had to be of the same hue as of the metropolis. A particular aspect of Western democracy that has been deemed problematic on the African continent is its adversarial form crystallised by open and vicious competition for power between political parties. First to reject this party-polity were the first generation of African leaders. Disastrously for them, both their theories and practices were to be discredited, and as the personae fell so did their theories. The prominent African philosopher Kwasi Wiredu has led a sustained onslaught on the party-polity. He has attempted to show that this polity has several problems including that it is a poor version of democracy as well as that its structures promote considerable harm in the form of unb ridled competition for power, which all result in exclusionary politics. In the process of arguing for a more inclusive polity, consensual democracy, Wiredu has set his sights on outlining the precise nature of how such a polity is more democratic while at the same time shunning party politics. What I seek to do here is to present an assessment of some of Wiredu’s arguments in support of consensus as a non-party polity. I wish to argue that the attempt of doing away with party politics is not very compelling. I also wish to show why those who read Wiredu’s position as a return to a one-party state should receive a sympathetic hearing.